The association between maternal anaemia in the third trimester and low birth weight neonates: a cross-sectional study - Maida Qazi; Bilal Ahmed Khan; Vijay Kumar; Mahnoor Amin; Mahnoor Shaikh; Kanza Ateeque (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the association between maternal anaemia during the third trimester and low birthweight babies. Method: The prospective, cross-sectional study was conducted from August to October 2024 at Lyari General Hospital, Karachi, and comprised women with singleton, term pregnancies. Using a structured questionnaire, sociodemographic data and haemoglobin levels of the mothers in the 3rd trimester were recorded. Maternal anaemia’s potential association with body mass index, maternal age, child birthweight, gestational age at delivery, and nulliparity was explored. Data was analysed using SPSS 26. Results: Of 314 pregnant women with mean age 27±5.88 years, 241(76.8%) were anaemic. Low birthweight (<2.5kg) was observed in 45(14.3%) neonates. A significant association (p<0.01) was found between maternal anaemia in the 3rd trimester and low birthweight in neonates. Conclusion: Low haemoglobin levels in the third trimester were found to be significantly associated with low birthweight of the neonate, with severe anaemia posing the highest risk. Key Words: Anaemia, Low birthweight, Gestational age, Body mass index, Parity.